Optimal Design Parameters for Supercritical Steam Power Plants - Victor-Eduard Cenușă; Ioana Opriș (Thermo)
Steam thermal power plants represent important energy production systems. Within the energy mix, these could allow flexible generation and the use of hybrid systems by integrating renewables. The optimum design solution and parameters allow higher energy efficiency and lower environmental impact. This paper analyzes single reheat supercritical steam power plants design solutions using a genetic heuristic algorithm. A multi-objective optimization was made to find the Pareto frontier that allows the maximization of the thermal cycle net efficiency and minimization of the specific investment in the power plant equipment. The Pareto population was split and analyzed depending on the total number of preheaters. The mean values and the standard deviations were found for the objective functions and main parameters. For the thermal cycle schemes with eight preheaters, the average optimal thermal cycle efficiency is (48.09 ± 0.16)%. Adding a preheater increases the average optimal thermal cycle efficiency by 0.64%, but also increases the average optimum specific investments by 7%. It emphasized the importance of choosing a proper ratio between the reheating and the main steam pressure. Schemes with eight and nine preheaters have an average optimum value of 0.178 ± 0.021 and 0.220 ± 0.011, respectively. The results comply with data from the literature.